Hanoï - Environs - Village du Kinh-Luoc Tombeau des Mandarins - Auteur inconnu (Wikimedia Commons, 1945)
Notice image issue de Wikimedia Commons. Titre: Hanoï - Environs - Village du Kinh-Luoc Tombeau des Mandarins. A postcard depicting the tomb of the Nguyn Dynasty Mandarin (and the Viceroy of Tonkin) Hoàng Cao Khi in the city of Hanoi, in the French protectorate of Tonkin.
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale